Pengaruh Kualitas Pelayanan, Pengetahuan Perpajakkan dan Biaya Kepatuhan pada Kepatuhan Wajib Pajak Kendaraan Bermotor - Tresnalyani, Ni Kadek Metri; Jati, I Ketut (E-Jurnal Akuntansi; Vol 24 No 1 (2018)DO - 10.24843/EJA.2018.v24.i01.p22, 2018)
The purpose of this study is to obtain empirical evidence of the effect of service quality, tax knowledge, and compliance costs on compliance of motor vehicle taxpayers in SAMSAT Office Denpasar City. The population in this research is all obligatory PKB active and registered in SAMSAT Office Denpasar City, that used 100 sample of responden. The sample was count by Slovin formula with accidental sampling method. The data was collected by questionnaire method and the data analysis technique used doubled linear regression. This research shows that service quality and tax knowledge have a positive effect on motor vehicle taxpayer compliance. While the cost of compliance has a negative effect on the compliance of motor vehicle taxpayers. Keywords: Quality of service, tax knowledge, compliance cost, taxpayer compliance